The potential contributions of geographic information science to the study of social determinants of health in Iran - Hamidreza Rabiei-Dastjerdi; Stephen A Matthews (Wolters Kluwer Medknow Publications, 2018)
Recent interest in the social determinants of health (SDOH) and the effects of neighborhood contexts on individual health and well-being has grown exponentially. In this brief communication, we describe recent developments in both analytical perspectives and methods that have opened up new opportunities for researchers interested in exploring neighborhoods and health research within a SDOH framework. We focus specifically on recent advances in geographic information science, statistical methods, and spatial analytical tools. We close with a discussion of how these recent developments have the potential to enhance SDOH research in Iran.